Adamantinoma of early stage in adult tibia: case report - Padilla Flores, Juan Roberto (2018)
0.4% of all primary bone tumors. Due to the rarity of this entity and its similarity with benign lesions, its diagnosis is sometimes delayed. We present the case of a 38-year-old female patient with a painful tumor in the left leg of 2 years of evolution, with radiological and histopathological studies that confirmed the diagnosis in the early stage.